Pelatihan Penggunaan Mesin Pengering Kopi Untuk Meningkatkan Keterampilan Petani Kopi - Nur Faizin; Zeni Ulma; Dafit Ari Prasetyo; Yuli Hananto; Cahyaning Nur Karimah (Journal of Community Development, 2023)
Improving human resource skills is one of the pillars in determining the increase in quality and quantity of production in a business. In the coffee plantation business sector, the skills of coffee farmers play an important role in the production process. The operation of the machines used is an absolute requirement for achieving effectiveness and efficiency in the process. One of them is a coffee drying machine obtained by the Sumber Kembang farmer group from previous community service activities. This must be accompanied by operating skills so that in this service activity training will be carried out on the use of coffee drying machines. The methods used were surveys, training and discussions. The result of this service activity is the achievement of increasing the skills of coffee farmers in terms of operating coffee drying machines. Achievement of service activities is carried out by providing feedback to partners in the form of questionnaires. The results of the questionnaire showed that respondents from partner members mostly gave positive responses to service activities in the form of coffee drying machine training.